Maintenance policies for protection systems subject to internal degradation and external shocks - RODRIGUES, Augusto José da Silva (2024)
Strategic decisions within maintenance management significantly impact business operations, affecting not only associated costs but also system reliability. In spite of this, although many maintenance models and policies have been developed for critical systems, little attention has been given to protection systems. These systems often remain inactive, with their functionalities activated only in emergency situations (demands). In contrast to critical systems, where failures can immediately disrupt operations, protection system failures are not self- announced. This intrinsic characteristic occasionally leads to the underestimation of the importance of these systems compared to critical ones. However, an unmet demand due to the non-functioning of a protection system can trigger disasters, ranging from environmental and structural impacts to loss of lives. Furthermore, most models developed for protection systems assume that they only fail due to an internal degradation process. However, shocks, potentially harmful external events, are common failure modes that can accelerate deterioration. Understanding the importance of the readiness of these systems, this work aimed to develop new maintenance policy models to support the correct definition of maintenance plans for protection systems subject to competitive failure modes: internal degradation and external shocks. The first two models were designed for protection systems with single components. The first model, following a failure mode according to a shot-noise process, was designed for systems in which its activation to meet a demand acts as an accelerator of the deterioration process. The second model deals with heterogeneous populations (weak and strong components). On the other hand, the third model was designed for two-component systems with stochastic dependence. The modelling of these latter two was conducted using the delay-time concept and the shock rate depends upon the state of the system, following a non-homogeneous Poisson process. Thus, three hybrid maintenance policies are introduced, integrating strategies of inspections and preventive replacement. Subsequently, numerical studies were conducted to compare the performance of the proposed policies with other classical policies from the literature, showing a significant potential for cost reduction in both cases. Finally, user-friendly web-based applications have been developed to allow readers to check the results or explore others.